Does fire severity difference create divergent plant communities in black spruce-Kalmia forests of eastern Canada? - Siegwart, Laura C. (2009)
After fire, some conifer-ericaceous plant communities in Western Europe and eastern North America have demonstrated divergent succession from traditional conifer stand replacement to Ericaceae-dominated community states. Divergence may be of function of species‟ responses to changes in fire severity as determined by the amount of residual organic matter (ROM) remaining after fire. ROM depth may act as an abiotic habitat filter to conifer species by physically inhibiting species establishment or through chemical afterlife effects in the unburned organic matter. If post-fire community assembly is predominantly determined by ROM depth, then post-fire species composition and their functional traits should correspond with the depth and distribution of ROM. But if species interactions are the primary constraint on community assembly, then post-fire species composition and their functional traits should be independent of the depth and distribution of ROM. I tested these predictions in black spruce (Picea mariana (Mill.) B.S.P.)-Kalmia (Kalmia angustifolia L.) plant communities of eastern Newfoundland among three post-fire plant community types (heath, wood savannah and forest) with similar pre-fire stand types (forest). To determine if the three communities were similar prior to fire, I reconstructed stand types by sampling unburned portions of adjacent stands and by compiling pre-fire forest resource inventory data. I quantified post-fire differences in species composition by determining percent cover of all vegetation along three 20 x 1 m belt transects in replicated 20 x 20 m plots. From the species list, I compiled functional trait information from the literature for each species, and weighted traits by the total cover of species that possessed a given trait. Species and trait response (total abundance, richness and diversity) was then compared using one-way ANOVA. Indicator analysis was also performed to characterize species and functional traits among communities. I estimated fire severity as ROM by taking soil cores sampled contiguously in one 20 x 1m belt transect from the replicated 20 x 20 m plots in each community. ROM was estimated by the depth of organic matter not consumed by the most recent fire under the uppermost charcoal layer. Multivariate ordination (Canonical correspondence analysis) and exponential growth and decay models were then used to test the effect of ROM on species composition and their functional traits. I found that the relative importance of abiotic and biotic filtering in post-fire community assembly was a function of ROM. When ROM was less than 2 cm, abiotic filtering favored the establishment of black spruce and other seed regenerating species, leading to black spruce recovery. When ROM was greater than 2 cm, substrate conditions and biotic interactions favored Kalmia and other vegetatively regenerating species, resulting in successional divergence. Also, when abiotic filtering was the predominant habitat constraint, it controlled species composition and functional traits directly by filtering species mode of regeneration, and indirectly through differences in the dominant species‟ performance between the heath and forest. The independence of species composition and functional traits to shallow ROM in the wood savannah suggests that priority effects may play an important role in determining the relative importance of abiotic vs. biotic filtering when ROM is around a threshold value (~2 cm).